SOCIAL-PSYCHOLOGICAL PREREQUISITES OF THE FORMATION OF ETHNIC IDENTITY AND MENTALITY OF THE INDIGENOUS ARMENIAN POPULATION OF ARTSAKH - Yaramishyan, Vitya (Modern Psychology, 2024)
The article discusses several psychological features in the formation of national identity, mentality, and core beliefs, using the example of Armenians from Artsakh. Based on research conducted with individuals born and living in Artsakh over the past three decades, it identifies the historically and culturally rooted factors that, according to the author, have a significant impact on the formation of national identity, national consciousness, and thought processes in times of crisis. As noted by Armenian and foreign researchers, since ancient times, the people of Karabakh have been known for their bravery, courage, resourcefulness, resilience, honesty, incorruptibility, and unwavering loyalty in their behavioral choices. Nature and history in Artsakh have shaped a community belonging to the Armenoid anthropological type, one that, spread throughout the world, can be easily recognized by its dynamism, self-sacrificing bravery, inclination toward courage, resilience that borders on tenacity, convictions that verge on stubbornness, and a patriarchal approach in family life. These admirable traits of the people of Artsakh seem to embody the ancient Armenian virtues. Passed down through generations, these human qualities have hardened and shaped the unique and distinctive character of the Armenian population of the region.